A hierarchical approach to measure service performance in the resort hotel’s service encounters / Yun Yang and Andrew Chan - Yang, Yun; Chan, Andrew (Faculty of Hotel and Management, Universiti Teknologi MARA, Selangor, Kampus Puncak Alam Campus, 2010)
Although a number of researchers have proposed models to better investigate service performance in the hospitality industry, many of them are still along the Oliver’s (1981) expectation-disconfirmation theory. To more effectively and directly measure service performance, the performance-based measurement of applying multilevel and multidimensional theory has been highly recommended in recent years. In view of the characteristics of service performance in the resort hotel, a hierarchical model that combined the concept of service encounters and Rust & Oliver’s (1994) three service dimensions is initially proposed in this study according to literature-based insights. Combining the results from in-depth interviews and reviews of the literature on the measurement scales of hospitality service performance, this study then identifies sub-dimensions and underlying attributes in the conceptual model. From perceiving service performance in the resort hotel, obvious distinctions and emphases that are different from those of the traditional or commercial hotel are also found in this study